Distributed Management in Crisis and Emergency Situations. Mathematical machines and systems - Sapaty, P.S. (Математичні машини і системи, 2019)
The purpose of this paper is to analyse and demonstrate possible application of the developed high-level Spatial Grasp Technology, SGT, and its Spatial Grasp Language, SGL, for dealing with different local and global crisis and emergency situations in dynamic distributed environments.